Evaluasi Desain UI pada Prototype Aplikasi Influencer Marketing "Endorsfy" dengan Metode SEQ - Gotra, Anak Agung Ngurah Mahadana Apta; Karyawati, Anak Agung Istri Ngurah Eka (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023, 2023)
The success of a digital product, relies heavily on the inseparable relationship between User Interface (UI) and User Experience (UX). Although UI is a fundamental aspect of UX, it's imperative to acknowledge that the UI's design, functionality, and ease of use are pivotal factors that can make or break a digital product's success. A top-notch UI design can significantly enhance the UX, while a deficient and convoluted UI can lead to a less-than-stellar user experience. In this study, we undertake the task of evaluating the UI quality of "Endorsfy" – an Influencer Marketing Mobile Application. We employ the Single Ease Question (SEQ) method and the Maze tool to assess the UI quality and determine if it meets the standards for optimal usability. Additionally, this evaluation will consider the usability aspect of the application to ensure that it delivers a seamless user experience. Our ultimate objective is to guarantee that "Endorsfy" achieves the highest standards for UI quality and usability, providing users with an unparalleled experience when using the application.